Expert Web System: Diagnosis of Visual Diseases - Boza-Chua, Alejandro; Gabriel-Gonzales, Karen; Andrade-Arenas, Laberiano (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Sight is one of the senses with the greatest sup- port for our daily life because the brain receives 80% of the information visually. However, it is one of the most neglected senses in Latin America, mainly in Peru. This is because since that in this country the sense of sight is related to the second disability with the highest percentage. Thus, 76% of the visually impaired population lost their sight due to lack of treatment or lack of early detection of any visual disease. For this reason, the present research work originated, which has the purpose of designing and implementing an expert web system oriented to the welfare of the vulnerable population regarding visual diseases and the care of the sense of sight. Therefore, the Buchanan methodology was used for the development of this project, which contains 5 phases of development and planning. This methodology allowed the identification of viable requirements for the expert web system, as well as the study of detailed solutions and design. Thus, it allowed the development of an expert web system that complies with the eye care, through early diagnosis. Finally, as a result of the present research work, it was obtained that the expert web system meets 88% of satisfaction, the value obtained through a questionnaire to a sample of 60 people, including patients and specialists of the company called MK Optical Center.